The genome of a Late Pleistocene human from a Clovis burial site in western Montana - Rasmussen, Morten; Anzick, Sarah L.; Waters, Michael R.; Skoglund, Pontus; DeGiorgio, Michael; Stafford, Thomas W.; Rasmussen, Simon; Moltke, Ida; Albrechtsen, Anders; Doyle, Shane M.; Poznik, G. David; Gudmundsdottir, Valborg; et al. (Nature (London), 2014)
The first individual genome from the Clovis culture is presented; the origins and genetic legacy of the people who made Clovis tools have been under debate, and evidence here suggests that the individual is more closely related to all Native American populations than to any others, refuting the hypothesis that the Clovis people arrived via European (Solutrean) migration to the Americas. Ancient genome maps Native American ancestry The Clovis complex is an archaeological culture distributed widely in North America. Dating to around 13,000 years ago it is characterized by distinct stone tools including a spear blade known as the Clovis point. Just who made these tools has been a subject of much speculation based on sparse information. There is now more to go on with the publication of the first genome sequence of an ancient North American individual. The genome is that of a male infant (Anzick-1) from the Clovis burial at the Anzick site in Montana. The partial skeleton, buried about 12,600 years ago, was found in association with scores of ochre-painted stone tools. Its genome is from a population from which contemporary Native Americans are descended and is more closely related to all indigenous American populations than to any others. These findings refute the hypothesis that the Clovis people migrated from Europe, are consistent with a human occupation of the Americas a few thousand years before Clovis, and suggest that contemporary Native Americans are descendants of the first people to settle successfully in the Americas. Clovis, with its distinctive biface, blade and osseous technologies, is the oldest widespread archaeological complex defined in North America, dating from 11,100 to 10,700 14 C years before present ( bp) (13,000 to 12,600 calendar years bp ) 1 , 2 . Nearly 50 years of archaeological research point to the Clovis complex as having developed south of the North American ice sheets from an ancestral technology 3 . However, both the origins and the genetic legacy of the people who manufactured Clovis tools remain under debate. It is generally believed that these people ultimately derived from Asia and were directly related to contemporary Native Americans 2 . An alternative, Solutrean, hypothesis posits that the Clovis predecessors emigrated from southwestern Europe during the Last Glacial Maximum 4 . Here we report the genome sequence of a male infant (Anzick-1) recovered from the Anzick burial site in western Montana. The human bones date to 10,705 ± 35 14 C years bp (approximately 12,707–12,556 calendar years bp ) and were directly associated with Clovis tools. We sequenced the genome to an average depth of 14.4× and show that the gene flow from the Siberian Upper Palaeolithic Mal’ta population 5 into Native American ancestors is also shared by the Anzick-1 individual and thus happened before 12,600 years bp . We also show that the Anzick-1 individual is more closely related to all indigenous American populations than to any other group. Our data are compatible with the hypothesis that Anzick-1 belonged to a population directly ancestral to many contemporary Native Americans. Finally, we find evidence of a deep divergence in Native American populations that predates the Anzick-1 individual.